Property managers’ competencies in managing green certified office building in Klang Valley / Syamim Jaafar - Jaafar, Syamim (2020)
The burgeoning green building development in Malaysia has drawn the attention of the property management industry on the importance of its active role in sustaining the “greenness” of green building throughout its life cycle. Moreover, many building owners believe that property management may increase the capital value of their buildings and at the same time maintaining its life span. However, the lack of property managers’ competencies has overshadowed the benefits of the green building development. A property manager faces challenges in the management activity due to lacking knowledge and skill of green material and technology adopted in the green building make it difficult to manage. Therefore, the objectives of the research were to identify the competencies needed for property managers in managing a green certified office building, to determine the key competencies for property managers, and to evaluate the relationship between competencies and property management performance of green certified office buildings. The scope of this study is the property manager who involved in managing 44 green certified offices building listed under the Green Building Index (GBI) in Klang Valley, Malaysia. The study uses a quantitative method and purposive sampling technique. The research outlines 56 KSAOs items for property manager and 12 dimension of property management performance based on review of existing literature review and validated by three expert property managers practicing property management in green building. Questionnaires were distributed through email and a response rate of 62% was obtained. The results showed that all the KSAOs items listed were rated as important for a property manager in managing green certified office buildings. An Exploratory Factor Analysis (EFA) was also applied and extracts 36 items on four main categories, namely Green Skill, Ability, Knowledge, and Personality which explained 47.1% of the property manager competencies. The result shows that technical and technology skill items, oral expression and oral comprehensive items, self-confident as well as business and marketing management are the key competencies that has contributed to property managers. A path analysis (SmartPLS version 3) was also conducted and the study found that Green Skill and Ability have a significant relationship with property management performance in green certified office building. The findings may provide significant input related to property manager professions such as increasing their knowledge and skills leading to a higher level of professionalism in Malaysia.